Phytochemical Composition of Selaginella spp. from Java Island Indonesia (Makara Journal of Science, 2012)
For a long time, people in West Java, Indonesia have used Selaginella as a traditional cure for several ailments including fever, minor wounds, broken bones, women’s health disorders or postnatal bleeding. However, information on the active compounds of the plant from Java Island has not been fully expounded. The objective of the research was to reveal the diversity of bioactive compounds and amentoflavone content of Selaginella from Java Island in order to optimize the use of this plant as a medicinal plant. Selaginella plants collected from 29 locations in Java were extracted and subjected to colorimetric and thin layer chromatography test to qualitatively analyze the bioactive compounds of alkaloid, phenol, and steroid. In addition, high performance liquid chromatography was performed to analyze the amentofalvone content of Selaginella extract. The research result showed that all the examined Selaginella species contained alkaloid, flavonoid, saponin, tannin, and steroid, but they did not contain hydroquinone. Seven of them contained the biflavonoid type of amentoflavone. The highest amentoflavone concentration, 6.87 ppm, was found in S. subalpina that originated from Gedung Songo, Central Java. Those results indicated that more than one Selaginella species originating from Java Island had marked potential for use as medicinal plants.